DARE-AKI: Does enhanced Detection, clinical Analytics, Referral and Early therapy improve AKI outcomes in secondary care? - Alistair Connell (Frontiers in Public Health, 2015)
Background Acute Kidney Injury AKI occurs in up to 15% of hospital admissions , and is associated with an increased risk of death1: some 40,000 excess deaths/year in England are attributed to AKI1. It is also associated with an increased length of stay2, and the development of chronic kidney disease3. This is expensive- one recent economic analysis estimated the associated healthcare costs for England to be over £1bn/year2. Whilst poor outcomes relate in part to patients’ underlying disease states, much of this impact appears causally attributable to AKI itself4. It may be possible to halt its progression and prevent its clinical sequelae with timely and appropriate intervention5. Recent drives to reduce ‘avoidable harm’ in hospitals are underpinned by both early identification of deteriorating patients, and rapid and appropriate intervention. Despite this, the 2009 NCEPOD enquiry reported delays in the recognition of AKI to be commonplace, and care of patients with established AKI to be “good” less than half of the time6.